STUDENTS’ TRANSLATION COMPETENCE THROUGH IDIOMATIC TRANSLATION AT SMA NEGERI 1 LANGSA - Rasid Ritonga, Mhd.; Ely Shinta, Marda; Habsari Pratiwi, Siti (JL3T (Journal of Linguistics, Literature and Language Teaching), 2016)
The aim of this research is to find out the effect of students’ translation competence through the techique of idiomatic translation at SMA Negeri 1 Langsa with class XI IPA 6 as experimental group and XI IPA 7 as control group. The study was carried out by quasy experimental design. The data was collected through translation test. The study reveals that idiomatic translation improves students’ translation competence. The statistical analysis shows a significant difference between the two groups. The statistical analysis shows that t observed is higher than t table at the significant level of 5%. Therefore, the Ho is rejected and Ha is accepted. The study suggests that this technique be applied in teaching translation in EFL classes.